Crustal imaging of northern Harrat Rahat, Saudi Arabia, from ambient noise tomography. Issue 3 (19th August 2019) - Civilini, F; Mooney, W D; Savage, M K; Townend, J; Zahran, H
SUMMARY: Harrat Rahat is a volcanic field located in west-central Saudi Arabia and is the site of the most recent eruption in the country (1256 CE). An earthquake swarm at a nearby volcanic field in 2009 prompted the need for new hazard models for this region, which includes the holy city of Medina. Tomography studies can be used to infer material properties of the subsurface such as partial melt, and are instrumental for volcanic hazard assessment. Regional earthquakes have been used to determine mantle structure, but such crustal models are often hindered by an insufficient number of earthquakes in the plate interior. We use ambient seismic noise to compute Rayleigh and Love surface-wave dispersion maps between 5 and 12 s for northern Harrat Rahat. The surface-wave maps are inverted to produce shear-wave velocities using a neighbourhood algorithm and interpolated into a pseudo-3-D model. The distributions of surface-wave and shear-wave velocities are heterogenous, varying between ±3 and 8 per cent. However, low velocities are not restricted to the Harrat. We observed a difference between Rayleigh- and Love-wave velocities that extends north from the site of the 1256 CE eruption and coincides with a low gravity anomaly. We obtain a shear-wave velocity increase of 10–15 per cent between 15 and 25 km depth consistent with the Conrad discontinuity, the interface between andesitic upper crust and the mafic lower crust of the Arabian Shield. The average velocities of the upper and lower crust are estimated to be 3.64 and 3.95 km s –1 using Rayleigh waves and 3.53 and 4.16 km s –1 using Love waves, which are in good agreement with the results of other geophysical studies of this area. The magnitude of the low-velocity anomalies, their location away from the Harrat, and the lack of reversals in the shear-velocity inversions suggest that the presence of a crustal magma chamber is not likely. If a magma chamber exists, it is smaller than can be imaged with a secondary microseism source (approximately 15 km wavelength), deeper than 30 km, or shallower than 5 km with a small velocity contrast.